Addressing barriers to addiction recovery services in the Northwest Territories, Canada - Bryany Denning; Barbara Broers; Pertice Moffitt (International Journal of Circumpolar Health)
The Northwest Territories, Canada, has high rates of alcohol- and drug-related hospitalisations and deaths. There is considerable debate over how to provide substance use recovery services in this region, due to its small, culturally diverse population. The aim of this study was to examine demographic differences in ethnicity, gender and sex for individuals in the barriers to accessing services, supports to stay in recovery, and reasons they struggled to stay in recovery. A total of 439 respondents completed online and paper-based surveys on their experiences accessing recovery services in the Northwest Territories. A mixed methods approach was applied, in which Fisher’s exact test was applied to test for statistically significant demographic differences in quantitative responses, and themed analysis was performed using deductive coding using written survey responses. Several statistically significant demographic differences were identified in barriers to services, supports to recovery, and barriers to staying in recovery. Cultural incongruity, and the importance of social support to substance use disorder recovery, were identified as key themes that emerged in qualitative analysis. There is a need for community-based, culturally safe, and family-inclusive holistic supports at the community level to address substance use issues in the NT, including more informal confidential supports and efforts to reduce stigma and normalise and celebrate recovery.